Myocardial infarction of the "forgotten chamber of the heart" — the right atrium: a clinical case - N. I. Kornev; K. G. Pereverzeva; S. S. Yakushin; I. B. Glukhovets (Рациональная фармакотерапия в кардиологии)
The incidence of atrial myocardial infarction (MI) varies widely, from 0.7 to 42%. This indicates that atrial MI is an overlooked rather than a rare pathology. Ischemic myocardial damage due to atherosclerotic lesions of the coronary vessels is characteristic of left atrial MI, which is often combined with left ventricular MI. In right atrial (RA) MI, the main pathogenesis link is RA overload, which occurs due to pulmonary hypertension. Isolated atrial MI is a poorly understood issue in modern cardiology; however, it may have independent clinical significance. However, there is no unified approach to pathogenesis, and there is no specific diagnostics or treatment. The article presents a clinical case of isolated RA MI (isolated necrosis of the right cardiac auricle) that developed as a result of a series of sequential events triggered by acute decompensation of chronic heart failure (CHF). The cause of this acute decompensation of CHF remains debatable. Probably, the leading contribution to CHF decompensation was made by a previous left ventricular MI with damage to the infarct-related right coronary artery basin, which causes RA involvement. Acute decompensation of CHF led to the development of deep vein thrombosis of the lower extremities. Pulmonary embolism developed as a result of deep vein thrombosis of the lower extremities and caused pulmonary hypertension, which in turn served as the basis for the development of RA MI. Due to the small thickness of the atrial wall, acute ischemic damage to the RA in this clinical case led to myomalacia and perforation of the RA wall. Due to the complexity of lifetime diagnosis of isolated atrial myocardial damage and scant clinical symptoms, this condition requires special attention and should be covered in order to develop generally accepted views on the management of patients with this pathology and to determine a list of effective treatment measures aimed at saving the patient’s life.